In vitro 3-D multicellular models for cytotoxicity assay and drug screening. Issue 6 (June 2016) - Zang, Ru; Zhang, Xudong; Sun, Jianxin; Yang, Shang-Tian
Graphical abstract: Microbioreactors on modified 384-well plate with 3-D PET scaffold for growing cells expressing green fluorescent protein (GFP) in response to drug as a multicellular model for high throughput cytotoxicity and drug efficacy screening. Highlights: A high-throughput drug screening system with autofluorescent mES and human colon cancer cells. Cells were cultured in 3-D PET scaffolds mimicking in vivo microenvironment. The 3-D cultures could be used as more reliable models for assessing dose-dependent drug responses. The in vitro HT-29 cell model could predict the effective dosage of 5-FU for treating colon cancer. This system should have applications in early-stage drug discovery and toxicological evaluation. Abstract: Three-dimensional (3-D) cell culture models have been developed to improve drug screening and predictive efficacy. In this study, a high-throughput drug screening system with autofluorescent cells cultured in 3-D polyethylene terephthalate (PET) scaffolds mimicking in vivo microenvironment was developed. Using a modified microbioreactor platform designed specifically for 3-D cell cultures, three commonly used drugs, 5-fluorouracil (5-FU), gemcitabine, and sodium butyrate, were tested for their cytotoxicity on 3-D mouse embryonic stem (mES) cells and human colon cancer HT-29 cells, respectively. In general, 3-D cultures with multicellular structures exhibited similar expression in Ki-67 (a proliferation marker) and p27 kip1 (a quiescence marker) as compared to fresh tissues, and gave better predictive values of effective drug dosage in vivo . The 3-D multicellular mES and HT-29 cultures could be used as more reliable models for assessing dose-dependent drug responses, potentially reducing or partially replacing animal experiments, and thus should have applications in the early-stage drug discovery as well as toxicological evaluation of chemical compounds.